Особенности пульсирующих струй жидкости высокой скорости - Семко, А. Н.; Ягудина, Н. И. (НТУ "ХПИ", 2015)
В работе в акустической и газодинамической постановках исследованы процессы в импульсном генераторе струй жидкости. В акустической постановке рассматривалась одномерная задача без учета движения поршня и истечения струи. В газодинамической постановке численно решалась одномерная и осесимметричная задача с учетом движения поршня, истечения струи и кавитации жидкости. Проведено сравнение результатов расчетов для разных моделей движения жидкости, сделаны соответствующие выводы. Показано, что пульсации скорости струи связаны с волновыми процессами в установке.

The processes in a pulse generator of liquid jets were investigated in acoustic and gas-dynamic settings. In the acoustic setting a one-dimensional problem was considered without taking into account the piston movement and the jet outflow. In the gas-dynamic setting a one-dimensional and axisymmetric problem was solved numerically with taking into account the piston movement, jet outflow and liquid cavitation. The results of calculations for different models of fluid motion were compared. The appropriate conclusions were made. It was shown that the jet velocity pulsations were related to the wave processes in the installation.
Features of pulsing liquid jets of high speed
Keywords: жидкие диски; импульсный генератор струй; кавитация; численное моделирование; pulsing jets of liquid; liquid disks; pulse generator of jets; cavitation; numerical modeling